The impact of strategic ventilation adjustments on stress responses in horses housed full-time in a vector-protected barn during the African horse sickness outbreak in Thailand. (23rd February 2023) - Poochipakorn, Chanoknun; Joongpan, Weena; Tongsangiam, Pongphon; Phooseerit, Areeya; Leelahapongsathon, Kansuda; Chanda, Metha
Abstract: The severe outbreak of African horse sickness (AHS) in Thailand has forced horses to reside full-time inside barns that are covered by a small mesh net to prevent minuscule AHS insect vectors from gaining access. However, housing in the net-covered barn induces stress in horses, which compromises their welfare. Implementing strategic airflow adjustment while retaining the vector-protection characteristics has been proposed to help alleviate this problem. The present study aimed to investigate the effect of strategic ventilation adjustment on blood cortisol levels, heart rate and behaviour in horses in a vector-protected barn. Nine horses underwent two sequential stabling conditions: vector-protected barn housing and housing in a barn in which the air ventilation was explicitly adjusted. Heart rate was higher in the afternoon in horses housed in the barn without ventilation adjustment, whereas no change was observed in the barn with ventilation adjustment. The vector-protected housing increased the horses' behavioural scores. Blood cortisol level declined over time, and an earlier decrease was detected at 1400h in the barn with ventilation adjustment. Although airflow adjustment did not appear to statistically alter the stress response in horses during housing in the vector-protected barn, an earlier decline in cortisol level alongside an unchanged heart rate in horses during the day may indicate the positive impact of ventilation adjustment within the vector-protected barn. With limited options to reduce stress or discomfort in horses, this strategic protocol could, at least in part, be applied to managing horses' welfare during the AHS outbreak.